Guiding the learner's cognitive processing of a narrated animation. (October 2020) - Wang, Fuxing; Zhao, Tingting; Mayer, Richard E.; Wang, Yuxin
Abstract: In this study, three experiments were conducted to explore whether adding eye movement modeling examples (EMME) to a short narrated animation could facilitate visual processing during multimedia learning and learning outcomes, and whether the effects of EMME depended on the pace of lesson or prior knowledge level of the learners. In Experiment 1, college students viewed a system-paced animation on synaptic transmission that either did or did not include EMME. The EMME group paid more attention to relevant elements and performed better on learning outcomes. In Experiment 2, EMME facilitated visual processing and learning outcomes with system-pacing but not learner-pacing. In Experiment 3, both low and high knowledge learners showed improved visual processing and learning outcomes with EMME. In conclusion, adding visual signaling (or cueing) in the form of EMME can guide visual processing and improve learning outcomes in multimedia learning with a short lesson. Highlights: Three experiments explored the effects of eye movement modeling examples (EMME). EMME guided attention in learning from instructional animations. The EMME group performed better on learning outcomes than the no EMME group. Adding EMME facilitated learning outcomes with system-pacing but not learner-pacing. The effectiveness of EMME was not moderated by the learners' prior knowledge.